DIGITAL FARMING AND PRODUCTIVITY EFFECT: “THE SMART VILLAGE” IN TURKEY - ŞENKAYAS Hüseyin (Annals of the University of Oradea: Economic Science, 2019)
Food loss and unproductive farming are the main problems in agricultural activities in Turkey. During farming, harvesting and postharvest processes substantial losses take place. The existence of human beings depends on the supply of adequate food. Agricultural activities require detailed care and irrigation, hoeing, fertilization, harvesting etc. are vital problems for farmers. They spend all their time and energy for farming but they get very little. Also The reaction time of production is longer, depending on the variety and breadth of Turkey's climatic characteristics of agricultural land. This results in low efficiency and productivity in agriculture. In order to mitigate these negativity, institutions are trying to put forth new methods most of which are technology related. Digitilization and Internet of Things can be the the most rational methods to solve this problem. Agriculture 4.0, digital farming, smart farming are some of the concepts derived from Industry 4.0 logic and some institutions in Turkey try to help family farmers practice these innovations in their agricultural activities for higher efficiency. “Vodafone Smart Village” which was founded by TABIT (Agricultural Information and Communication Technologies) in Aydın province in Turkey is the first and only comprehensive sample for this purpose. The technologies used in the village provided a great advantage in agriculture and animal breeding. With the support of advanced technology and internet of things, innovations and developments are recorded and it aims to be a new generation professional gate of farming in the future. This is a new generation of rural life model, combining traditional farming methods with the possibilities of advanced technology, increasing production efficiency through information and communication technologies, and making the manufacturer's social life standards elevated with qualified knowledge. Economical objectives of the Smart Farm are at least 20% savings in plant production costs, save at least 22% on livestock costs, 30% revenue growth in livestock, 10% increase in total output, and within the scope of this information, annual revenue increase of 40.000 TL per household is 2 years. This study aims to put forth the productivity effects of various tecnologies and methods used in family farming in a small village. For this purpose, a questionnaire was applied to randomly selected male and female farmers living in the Smart Village. Findings are evaluated in terms of demographic status, education level, developping farming skills, access to information, use of technology, improvement of quality and quantity of products, and effect on productivity.